A lignin carbon-supported single metal nickel heterojunction composite material and its preparation method and application
By constructing a nickel-based heterojunction structure in the lignin phosphating modification of lignin alkali, the problems of high energy consumption and high cost in the conversion of lignocellulose biomass in the prior art are solved, and high-efficiency photothermal catalytic hydrogen evolution and biomass oxidation are achieved, with wide application potential.
Patent Information
- Application Number
- CN202411571201.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-06
AI Technical Summary
When converting lignocellulosic biomass into chemical fuels or high value-added chemicals, the problems of high energy consumption, complex product composition and high product purification costs are difficult to achieve efficient and low-cost biomass utilization.
The alkali lignin phosphating modification is used as the carbon support precursor, and synchronous oxidation and phosphation are synchronized through segmented calcination in N2-CO2 atmosphere to form a nickel-based heterojunction structure, and a lignin carbon-supported single metal nickel heterojunction composite material is prepared.
The composite material has a high specific surface area, excellent electron transport efficiency and strong light absorption capacity. It can significantly improve the photothermal catalytic hydrogen evolution performance and biomass oxidation activity without adding precious metal catalysts, and achieve efficient and low-cost biomass utilization.
Smart Images

Figure CN119076029B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic hybrid composite materials, and particularly relates to a lignin carbon-supported single metal nickel heterojunction composite material and a preparation method and application thereof. Background Art
[0002] In recent years, with the development of economy and the improvement of industrialization level, the demand for fossil fuels such as coal, oil and natural gas has been expanding, but the large-scale consumption of these fossil resources has caused serious environmental problems. In addition, driven by global warming and growing energy demand, expanding the development and application of renewable energy (including biomass energy, hydropower, wind energy and solar energy) and reducing dependence on fossil fuels are crucial to building a sustainable society. Among these renewable energy sources, biomass energy is a recognized renewable carbon pool and the fourth largest resource after the three major fossil energy sources. It has aroused great interest because of its short regeneration cycle, large output and wide distribution. Known biomass includes animal and plant resources represented by green plants, animals and domestic waste. Among them, the largest amount of biomass exists in the form of lignocellulose, with an annual output of more than 1.7× 10 14 kg. Currently, some new strategies (such as value-added, enzymatic hydrolysis, and thermal catalysis) have been developed to convert lignocellulosic biomass into chemical fuels or high-value-added chemicals, but these methods are limited by high energy consumption, complex product composition, and high product purification costs. Therefore, exploring green strategies for the utilization of lignocellulosic biomass remains a huge challenge.
[0003] Recently, photothermal catalytic oxidation coupled with hydrogen evolution from lignocellulosic biomass is a new method for hydrogen production. In this method, semiconductor materials photothermally catalyze H 2 The photogenerated electrons can convert H 2 O decomposes protons to form H 2 , while the holes oxidize the lignocellulosic biomass into organic matter, achieving the purpose of efficient hydrogen evolution and high-value oxidation.
[0004] Transition metal phosphides (such as nickel phosphide and iron phosphide) have the advantages of highly controllable geometric structure and electronic band structure, and low adsorption energy for hydrogen, and are widely used in hydrogen evolution reactions. The Ni-P structure effectively regulates the charge distribution, reduces the recombination of photogenerated carriers, and improves the performance of photothermal catalytic hydrogen evolution. However, in photothermal catalytic redox coupling reactions, the activity of a single active component is usually limited. Therefore, it is particularly important to construct a bifunctional active center. Compared with the introduction of other complex components, it is more beneficial to construct a bifunctional heterostructure with a single metal catalyst precursor, which has higher application value. Nickel oxide is a p-type semiconductor material with a band gap energy of ~3.5 eV and is widely used in redox reactions.
[0005] Lignin has attracted extensive attention in carbon materials due to its high carbon content, low cost and unique network structure. However, simple pyrolysis of biomass alone usually results in limited surface area, insufficient porosity, and poor wettability and conductivity. Heteroatom doping can effectively increase specific surface area, conductivity and other properties, regulate the structure to expose more active sites, and improve catalytic efficiency. Summary of the invention
[0006] In order to overcome the shortcomings and deficiencies in the prior art, the primary purpose of the present invention is to provide a method for preparing a lignin carbon-supported single metal nickel heterojunction composite material. The method first uses alkali lignin as a carbon carrier precursor by phosphating, which can not only improve the electron transfer efficiency and regulate the morphology of the carbon carrier, but also serve as a phosphorus source for the nickel phosphide phase; then, N 2 -CO 2 The nickel-based heterojunction structure is formed by simultaneous oxidation and phosphating in the atmosphere, and a composite material with excellent catalytic performance, easy recycling and reusability is obtained. This composite material is different from ordinary semiconductor heterojunction composite materials. The carbon carrier can increase the specific surface area of the composite material and accelerate the separation and transmission of photogenerated electrons and holes. The heterostructure of nickel oxide and nickel phosphide synergistically promotes redox performance.
[0007] Another object of the present invention is to provide a lignin carbon-supported single metal nickel heterojunction composite material prepared by the above-mentioned preparation method; the composite material has the advantages of large specific surface area, high electron transfer efficiency, strong light absorption ability, etc., and can be widely used in the field of photothermal catalysis and used for the research of efficient photothermal catalytic biomass hydrogen evolution process.
[0008] Another object of the present invention is to provide an application of the above-mentioned lignin carbon-supported single metal nickel heterojunction composite material in the field of lignin photothermal catalytic hydrogen evolution; during the application process, nickel oxide and nickel phosphide are loaded on the modified lignin carbon, which can promote the photothermal hydrogen evolution performance of lignin and oxidize lignin to obtain some high-value products.
[0009] The purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing a lignin carbon-supported single metal nickel heterojunction composite material is divided into two steps. The first step is to mechanically mix alkali lignin and a phosphorus source and then heat them at low temperature and N 2 In the second step, the carrier and nickel salt are prepared by deposition to obtain a precursor, which is then heated to high temperature and CO 2 The composite material is obtained by calcining in atmosphere.
[0011] A method for preparing a lignin carbon-supported single metal nickel heterojunction composite material comprises the following steps:
[0012] (1) mixing alkali lignin and a phosphorus source, taking them out after mechanical ball milling, and drying them to obtain a mixture powder;
[0013] (2) Place the mixture powder obtained in step (1) into a tube furnace at N 2 The phosphating modified lignin carbon carrier is obtained by calcining at a low temperature of 200-400 °C in an atmosphere;
[0014] (3) adding nickel nitrate and the phosphorus-modified lignin carbon carrier obtained in step (2) into deionized water and mixing them evenly, then adding urea solution dropwise thereto, transferring the obtained mixed solution into an oil bath pot, heating for reaction, taking out, filtering, washing, and drying to obtain a lignin carbon-supported nickel composite material precursor;
[0015] (4) Place the lignin carbon-supported nickel composite material precursor obtained in step (3) into a tube furnace and heat it under CO 2 The lignin carbon-supported single metal nickel heterojunction composite material was obtained by calcining at a high temperature of 600-800 °C in an atmosphere.
[0016] The phosphorus source in step (1) is one of phytic acid, sodium hypophosphite and ammonium dihydrogen phosphate, preferably sodium hypophosphite; the mass ratio of the phosphorus source to alkali lignin is 1:2 to 2:2.
[0017] The rotation speed of the mechanical ball mill in step (1) is 600 rpm, and the ball milling time is 1 h.
[0018] The low-temperature calcination in step (2) is to increase the temperature to 400°C at a heating rate of 5°C / min and calcine for 3h.
[0019] In step (3), the amount of nickel nitrate used is 0.55-1.23 g, the amount of the phosphating modified lignin carbon carrier used is 1 g, and the amount of deionized water used is 30 ml; the urea solution is obtained by dissolving 3.4-7.6 g urea in 30 ml deionized water; the temperature of the heating reaction is 70°C, and the reaction time is 10 h.
[0020] The drying temperature in step (3) is 75°C and the drying time is 10 h.
[0021] The high temperature calcination in step (4) is calcination at 600°C for 3h.
[0022] A lignin carbon-supported single metal nickel heterojunction composite material prepared by the above method, wherein the composite material is a phosphated porous carbon carrier mainly composed of mesopores, and has a specific surface area of 240.5 m 2 / g, which is conducive to exposing more active sites; without adding precious metal catalysts, the hydrogen evolution rate is 3164.4 μmol·g at 200 ℃ under simulated sunlight. catThis high-efficiency photothermal catalytic performance is mainly based on the close contact of nickel phosphide, nickel oxide and carbon support to form an np heterojunction. The photoexcited electrons of the carbon support can migrate to the nickel phosphide with a low work function, thereby promoting the separation and transfer of carriers; at the same time, with the help of photothermal synergy, the catalytic hydrogen evolution coupled with efficient oxidation of biomass is improved.
[0023] The above-mentioned lignin carbon-supported single metal nickel heterojunction composite material is used in the field of lignin photothermal catalytic hydrogen evolution.
[0024] Principle of the present invention:
[0025] The construction of nickel phosphide / nickel oxide heterostructure based on single metal Ni-based catalyst has high feasibility and application potential. Since nickel phosphide and nickel oxide have different work functions, they can form a curved band when they contact each other, which promotes the transmission of photogenerated carriers and effectively inhibits their recombination. It plays an efficient synergistic role in the photothermal catalytic reduction and oxidation reaction process, improving the performance of reduced hydrogen evolution and high-value oxidation conversion of lignin biomass.
[0026] The phosphating modified lignin carbon used in the present invention can not only provide a phosphorus source, but also as a carrier, it has higher structural controllability and good electron transmission energy delivery compared to ordinary lignin carbon materials, accelerating the separation and transmission of photogenerated electrons and holes, thereby improving the efficiency of photothermal catalysis. Single metal nickel forms nickel oxide and nickel phosphide structures through a synchronous oxidation and phosphating process, solving the problem of lack of active function and slow reaction kinetics of nickel-based catalysts in the photothermal catalytic process. This material is applied to the field of photothermal catalysis, can effectively catalyze hydrogen evolution coupled with lignin biomass oxidation, can significantly improve its hydrogen evolution performance and obtain high-value oxidation products, and has potential application value in the field of lignin photothermal catalytic hydrogen evolution.
[0027] Compared with the prior art, the present invention has the following advantages and effects:
[0028] The present invention uses industrial alkali lignin as a carbon source, and obtains a lamellar stacked porous lignin carbon structure through simple and easy-to-operate step-by-step calcination, which provides a rich high-activity defect structure and is conducive to the construction and exposure of active sites; and through CO 2 The NiO-NiP heterojunction structure is obtained by the process of simultaneous oxidation and phosphating by calcination in atmosphere. The method of the present invention is easy to control, the raw materials are easy to obtain, the production cost is low, and the prepared lignin carbon-supported Ni heterojunction composite material has good photothermal catalytic performance, realizing the high-value utilization of lignin. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanning electron microscope image of the lignin carbon-supported single metal nickel heterojunction composite material prepared in Example 3.
[0030] Figure 2X-ray diffraction patterns of the lignin carbon-supported single metal nickel heterojunction composite materials prepared in Examples 1 to 3 and Examples 6 to 8.
[0031] Figure 3 Raman spectra of the lignin carbon-supported single metal nickel heterojunction composite materials prepared in Example 3, Example 6 and Example 8.
[0032] Figure 4 This is the Mott-Schottky spectrum of the lignin carbon-supported single metal nickel heterojunction composite material prepared in Example 1, Example 3, Example 6 and Example 8.
[0033] Figure 5 These are the experimental results of hydrogen evolution of the lignin model compound vanillyl alcohol by photothermal catalysis of the composite materials prepared in Examples 1 to 8.
[0034] Figure 6 These are the experimental results of the liquid phase products of the composite materials prepared in Examples 3, 5 and 8 by photothermal catalysis of the lignin model compound vanillyl alcohol. DETAILED DESCRIPTION
[0035] The present invention is further described below with reference to specific embodiments and drawings, but they should not be construed as limiting the present invention.
[0036] The materials used in the following examples can all be obtained from commercial channels.
[0037] Example 1
[0038] Weigh 6 g of alkali lignin and 3 g of phytic acid and mix them by mechanical ball milling at a speed of 600 rpm for 1 h. After the ball milled powder is dried, a mixture powder is obtained. The mixture powder is placed in a tube furnace and heated at N 2 In the atmosphere, the temperature was raised to 400 °C at a heating rate of 5 °C / min and calcined for 3h, and then cooled to room temperature to obtain a phosphorus-modified lignin carbon carrier. Weigh 7.6 g of urea and dissolve it in 30 ml of deionized water to obtain a urea solution for standby use; take 1 g of the phosphorus-modified lignin carbon carrier obtained above and 1.23 g of nickel nitrate hexahydrate and add them to 30 ml of deionized water, and add the prepared urea solution dropwise while stirring, and then transfer the obtained mixture to an oil bath pot and react at 70 °C for 10 h; after the reaction is completed, take out the reaction product and filter it, and place the obtained filter cake in a low-temperature oven to dry at 75 °C for 10 h to obtain a lignin carbon-supported nickel composite material precursor; put the lignin carbon-supported nickel composite material precursor into a tubular furnace and heat it in CO 2 The carbon was calcined at 600 °C for 3 h under atmosphere and cooled to room temperature to obtain a lignin carbon-supported single metal nickel heterojunction composite material.
[0039] Example 2
[0040] Weigh 6 g of alkali lignin and 3 g of diammonium dihydrogen phosphate and mix them by mechanical ball milling at a speed of 600 rpm for 1 h. After the ball milled powder is dried, a mixture powder is obtained. The mixture powder is placed in a tube furnace and heated at N 2 In the atmosphere, the temperature was raised to 400 °C at a heating rate of 5 °C / min and calcined for 3h, and then cooled to room temperature to obtain a phosphorus-modified lignin carbon carrier. Weigh 7.6 g of urea and add it to 30 ml of deionized water to obtain a urea solution for standby use; take 1 g of the phosphorus-modified lignin carbon carrier obtained above and 1.23 g of nickel nitrate hexahydrate and add them to 30 ml of deionized water, and add the prepared urea solution dropwise while stirring, and then transfer the obtained mixture to an oil bath pot and react at 70 °C for 10 h; after the reaction is completed, take out the reaction product and filter it, and place the obtained filter cake in a low-temperature oven to dry at a drying temperature of 75 °C for 10 h to obtain a lignin carbon-supported nickel composite material precursor; put the lignin carbon-supported nickel composite material precursor into a tubular furnace and heat it in a CO 2 The carbon was calcined at 600 °C for 3 h under atmosphere and cooled to room temperature to obtain a lignin carbon-supported single metal nickel heterojunction composite material.
[0041] Example 3
[0042] Weigh 6 g of alkali lignin and 3 g of sodium hypophosphite and mix them by mechanical ball milling at a speed of 600 rpm for 1 h. After the ball milled powder is dried, a mixture powder is obtained. The mixture powder is placed in a tube furnace and heated at N 2 In the atmosphere, the temperature was raised to 400 °C at a heating rate of 5 °C / min and calcined for 3h, and then cooled to room temperature to obtain a phosphorus-modified lignin carbon carrier. Weigh 7.6 g of urea and add it to 30 ml of deionized water to obtain a urea solution for standby use; take 1 g of the phosphorus-modified lignin carbon carrier obtained above and 1.23 g of nickel nitrate hexahydrate and add them to 30 ml of deionized water, and add the prepared urea solution dropwise while stirring, and then transfer the obtained mixture to an oil bath pot and react at 70 °C for 10 h; after the reaction is completed, take out the reaction product and filter it, and place the obtained filter cake in a low-temperature oven to dry at a drying temperature of 75 °C for 10 h to obtain a lignin carbon-supported nickel composite material precursor; put the lignin carbon-supported nickel composite material precursor into a tubular furnace and heat it in a CO 2 The carbon was calcined at 600 °C for 3 h under atmosphere and cooled to room temperature to obtain a lignin carbon-supported single metal nickel heterojunction composite material.
[0043] Example 4
[0044] Weigh 6 g of alkali lignin and put it into a tube furnace at N 2In an atmosphere, the temperature was raised to 400 °C at a heating rate of 5 °C / min and calcined for 3 h, and then cooled to room temperature to obtain a lignin carbon carrier. 3.4 g of urea was weighed and added to 30 ml of deionized water to obtain a urea solution for standby use; 1 g of the above-obtained lignin carbon carrier and 0.55 g of nickel nitrate hexahydrate were added to 30 ml of deionized water, and the above-prepared urea solution was added dropwise while stirring, and then the obtained mixture was transferred to an oil bath pot and reacted at 70 °C for 10 h; after the reaction was completed, the reaction product was taken out and filtered, and the obtained filter cake was placed in a low-temperature oven to dry at a drying temperature of 75 °C for 10 h; the dried solid powder was placed in a CO 2 The lignin carbon-supported single metal nickel composite material was obtained by calcining at 600 °C for 3 h under atmosphere and cooling to room temperature.
[0045] Example 5
[0046] Weigh 6 g of alkali lignin and put it into a tube furnace at N 2 In an atmosphere, the temperature was raised to 400 °C at a heating rate of 5 °C / min and calcined for 3h, and then cooled to room temperature to obtain a lignin carbon carrier. 7.6 g of urea was weighed and added to 30 ml of deionized water to obtain a urea solution for standby use; 1 g of the above-obtained lignin carbon carrier and 1.23 g of nickel nitrate hexahydrate were added to 30 ml of deionized water, and the above-prepared urea solution was added dropwise while stirring, and then the obtained mixture was transferred to an oil bath pot and reacted at 70 °C for 10 h; after the reaction, the reaction product was taken out and filtered, and the obtained filter cake was placed in a low-temperature oven to dry at 75 °C for 10 h; the dried solid powder was placed in a CO 2 The lignin carbon-supported single metal nickel composite material was obtained by calcining at 600 °C for 3 h under atmosphere and cooling to room temperature.
[0047] Example 6
[0048] Weigh 6 g of alkali lignin and 3 g of sodium hypophosphite and mix them by mechanical ball milling at a speed of 600 rpm for 1 h. After the ball milled powder is dried, a mixture powder is obtained. The mixture powder is placed in a tube furnace and heated at N 2In the atmosphere, the temperature was raised to 400 °C at a heating rate of 5 °C / min and calcined for 3h, and then cooled to room temperature to obtain a phosphorus-modified lignin carbon carrier. 3.4 g of urea was weighed and added to 30 ml of deionized water to obtain a urea solution for standby use; 1 g of the phosphorus-modified lignin carbon carrier obtained above and 0.55 g of nickel nitrate hexahydrate were added to 30 ml of deionized water, and the urea solution prepared above was added dropwise while stirring, and then the obtained mixture was transferred to an oil bath pot and reacted at 70 °C for 10 h; after the reaction was completed, the reaction product was taken out and filtered, and the obtained filter cake was placed in a low-temperature oven to dry at a drying temperature of 75 °C for 10 h to obtain a lignin carbon-supported nickel composite material precursor; the lignin carbon-supported nickel composite material precursor was placed in a tubular furnace and dried under CO 2 The carbon was calcined at 600 °C for 3 h under atmosphere and cooled to room temperature to obtain a lignin carbon-supported single metal nickel heterojunction composite material.
[0049] Example 7
[0050] Weigh 6 g of alkali lignin and 6 g of sodium hypophosphite and mix them by mechanical ball milling at a speed of 600 rpm for 1 h. After the ball milled powder is dried, a mixture powder is obtained. The mixture powder is placed in a tube furnace and heated at N 2 In the atmosphere, the temperature was raised to 400 °C at a heating rate of 5 °C / min and calcined for 3h, and then cooled to room temperature to obtain a phosphorus-modified lignin carbon carrier. 3.4 g of urea was weighed and added to 30 ml of deionized water to obtain a urea solution for standby use; 1 g of the phosphorus-modified lignin carbon carrier obtained above and 0.55 g of nickel nitrate hexahydrate were added to 30 ml of deionized water, and the urea solution prepared above was added dropwise while stirring, and then the obtained mixture was transferred to an oil bath pot and reacted at 70 °C for 10 h; after the reaction was completed, the reaction product was taken out and filtered, and the obtained filter cake was placed in a low-temperature oven to dry at a drying temperature of 75 °C and a drying time of 10 h to obtain a lignin carbon-supported nickel composite material precursor; the lignin carbon-supported nickel composite material precursor was placed in a tubular furnace and dried under CO 2 The carbon was calcined at 600 °C for 3 h under atmosphere and cooled to room temperature to obtain a lignin carbon-supported single metal nickel heterojunction composite material.
[0051] Example 8
[0052] Weigh 6 g of alkali lignin and 6 g of sodium hypophosphite and mix them by mechanical ball milling at a speed of 600 rpm for 1 h. After the ball milled powder is dried, a mixture powder is obtained. The mixture powder is placed in a tube furnace and heated at N 2In the atmosphere, the temperature was raised to 400 °C at a heating rate of 5 °C / min and calcined for 3h, and then cooled to room temperature to obtain a phosphorus-modified lignin carbon carrier. Weigh 7.6 g of urea and add it to 30 ml of deionized water to obtain a urea solution for standby use; take 1 g of the phosphorus-modified lignin carbon carrier obtained above and 1.23 g of nickel nitrate hexahydrate and add them to 30 ml of deionized water, and add the prepared urea solution dropwise while stirring, and then transfer the obtained mixture to an oil bath pot and react at 70 °C for 10 h; after the reaction is completed, take out the reaction product and filter it, and place the obtained filter cake in a low-temperature oven to dry at a drying temperature of 75 °C for 10 h to obtain a lignin carbon-supported nickel composite material precursor; put the lignin carbon-supported nickel composite material precursor into a tubular furnace and heat it in a CO 2 The carbon was calcined at 600 °C for 3 h under atmosphere and cooled to room temperature to obtain a lignin carbon-supported single metal nickel heterojunction composite material.
[0053] Embodiment effect description:
[0054] Figure 1 This is a SEM image of the material prepared in Example 3. It can be seen that a lamellar stacked porous lignin carbon structure is successfully obtained through step-by-step calcination, which is conducive to the construction and exposure of abundant active sites.
[0055] Figure 2 The XRD patterns of the lignin carbon-supported single metal nickel heterojunction composite materials prepared in Examples 1 to 3 and Examples 6 to 8 show the phases of nickel phosphide and Ni-OP, indicating that phosphorus doping and CO 2 Atmosphere calcination can effectively construct heterojunction structure. Phytic acid and diammonium phosphate are not as effective as sodium hypophosphite.
[0056] Figure 3 This is the Raman spectrum of the lignin carbon-supported single metal nickel heterojunction composite material prepared in Example 3, Example 6 and Example 8. From the figure, we can see the characteristic peaks D band (disordered structure) and G band (ordered structure) of the carbon material, proving that the lignin carbon material has been obtained, and the D / G intensity ratios of materials with different phosphorus contents are also different, indicating that appropriate phosphorus doping effectively constructs the surface defect structure of the carbon layer.
[0057] Figure 4 This is the Mott-Schottky spectrum of the lignin carbon-supported single metal nickel heterojunction composite material prepared in Example 1, Example 3, Example 6 and Example 8. It can be seen from the figure that the heterostructure has n-type and p-type semiconductor characteristics, and as the degree of phosphating increases, the semiconductor type transitions from p-type to n-type.
[0058] Figure 5The results of the hydrogen evolution experiment of the composite material prepared in Examples 1 to 8 by photothermal catalysis of the lignin model compound vanillyl alcohol. The reaction conditions are a photothermal batch reactor, 50 mg of the composite material, 0.5 mmol of vanillyl alcohol, 50 ml of water as the solvent, a temperature of 200°C, a light source of simulated sunlight (300W Xe-lamp AM 1.5G), and a reaction time of 3 hours. The results show that increasing the nickel content and the appropriate phosphorus ratio are beneficial to improving the hydrogen evolution activity.
[0059] Figure 6 The experimental results of the liquid phase product of the composite material photothermal catalysis lignin model compound vanillin prepared in Example 5, Example 3 and Example 8. The liquid phase product after the reaction was extracted and separated with dichloromethane, and quantitatively analyzed by gas chromatography internal standard method. The results showed that the vanillin was completely reacted after the reaction, the increase in the degree of phosphation can increase the content of high dehydrogenation product vanillin, the appropriate phosphorus content increases the content of polymer in the product, and the polymerization reaction can increase the amount of hydrogen evolution in the reaction.
[0060] The above embodiments are relatively suitable implementation modes of the present invention. The implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a lignin carbon-supported single metal nickel heterojunction composite material, characterized in that The steps include: (1) mixing alkali lignin and a phosphorus source, taking them out after mechanical ball milling, and drying them to obtain a mixture powder; the phosphorus source is one of phytic acid, sodium hypophosphite and diammonium phosphate; the mass ratio of the phosphorus source to the alkali lignin is 1:2 to 2:2; (2) placing the mixture powder obtained in step (1) into a tube furnace and heating the mixture to 400°C at a heating rate of 5°C / min in a N2 atmosphere for low-temperature calcination for 3 h to obtain a phosphating modified lignin carbon carrier; (3) adding nickel nitrate and the phosphorus-modified lignin carbon carrier obtained in step (2) into deionized water and mixing them evenly, then adding urea solution dropwise thereto, transferring the obtained mixed solution into an oil bath pot, heating for reaction, taking out, filtering, washing, and drying to obtain a lignin carbon-supported nickel composite material precursor; (4) The lignin carbon-supported nickel composite material precursor obtained in step (3) is placed in a tubular furnace and calcined at 600° C. for 3 h in a CO2 atmosphere to obtain a lignin carbon-supported single metal nickel heterojunction composite material.
2. The method for preparing a lignin carbon-supported single metal nickel heterojunction composite material according to claim 1, characterized in that: The phosphorus source in step (1) is sodium hypophosphite.
3. The method for preparing a lignin carbon-supported single metal nickel heterojunction composite material according to claim 1, characterized in that: The rotation speed of the mechanical ball mill in step (1) is 600 rpm, and the ball milling time is 1 h.
4. The method for preparing a lignin carbon-supported single metal nickel heterojunction composite material according to claim 1, characterized in that: In step (3), the amount of nickel nitrate used is 0.55-1.23 g, the amount of phosphating modified lignin carbon carrier used is 1 g, and the amount of deionized water used is 30 ml; the urea solution is obtained by dissolving 3.4-7.6 g urea in 30 ml deionized water; the temperature of the heating reaction is 70° C., and the reaction time is 10 h.
5. The method for preparing a lignin carbon-supported single metal nickel heterojunction composite material according to claim 1, characterized in that: The drying temperature in step (3) is 75°C and the drying time is 10 h.
6. A lignin carbon-supported single metal nickel heterojunction composite material prepared by the preparation method according to any one of claims 1 to 5.
7. Application of the lignin carbon-supported single metal nickel heterojunction composite material according to claim 6 in the field of lignin photothermal catalytic hydrogen evolution.
Citation Information
Patent Citations
Flexible inorganic composite nanofiber membrane photocatalyst as well as preparation method and application thereof
CN115245835A
Preparation method and application of metal-biomass carbon heterojunction type electrolyzed water catalyst
CN117779082A